Self-driving car: a step to the future of mobility - Islam, Mohammad Zahirul; Hannan, Mohammad Abdul; Waliuzzaman, A K M; Ahsan, Ali (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.